1978
DOI: 10.1288/00005537-197810000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric tracheostomy and associated complications

Abstract: A retrospective analysis of 123 pediatric tracheostomies reveals an overall complication rate of 33%. Immediate complications were present in 12% or 15 patients. The most frequent immediate complications were pneumomediastinum and pneumothorax. Delayed complications occurred in 24% or 30 patients. The most frequent delayed complications were subglottic stenosis, fused vocal cords, and tracheal granuloma. Four patients died because of tracheostomy-related complications. Age, underlying disease, and prior endotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 10 publications
1
39
1
Order By: Relevance
“…Data also support early weaning of mechanical ventilation within 48 h of early tracheostomy [2,6]. On the other hand, tracheostomy itself may result in various procedural complications ''early'' in a patient's course [7][8][9][10][11][12][13]. Some evidence also exists to suggest that early tracheostomy does not, in fact, improve outcome [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…Data also support early weaning of mechanical ventilation within 48 h of early tracheostomy [2,6]. On the other hand, tracheostomy itself may result in various procedural complications ''early'' in a patient's course [7][8][9][10][11][12][13]. Some evidence also exists to suggest that early tracheostomy does not, in fact, improve outcome [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…3 Gaudet et al showed a complication rate of 33% in a retrospective study of paediatric tracheostomies. 10 In our study we had no cases of mortality inspite of the incidence of complications being high.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, we are yet unable to evaluate the rate or severity of tracheal stenosis or of TCF. Tracheal stenosis is reported to occur in 12-17% of RT [9,11] and persistent TCF in 18-25% [1,5,11]. Koltai does not report on any cases of tracheal stenosis.…”
Section: Discussionmentioning
confidence: 95%
“…It has been recognized that tracheotomy-related complication rates are greater in younger children [5,9]. In several studies, up to 70% of infants less than 1 year old, have experienced at least one tracheotomy-related complication [5,9,10].…”
Section: Discussionmentioning
confidence: 99%